Parametrisation of the free energy of ATP binding to wild-type and mutant Kir6.2 potassium channels. - Moran, O; Grottesi, A; Chadburn, A; Tammaro, P (2013)
ATP-sensitive K(+) (K(ATP)) channels, comprised of pore-forming Kir6.x and regulatory SURx subunits, play important roles in many cellular functions; because of their sensitivity to inhibition by intracellular ATP, K(ATP) channels provide a link between cell metabolism and membrane electrical activity. We constructed structural homology models of Kir6.2 and a series of Kir6.2 channels carrying mutations within the putative ATP-binding site. Computational docking was carried out to determine the conformation of ATP in its binding site. The Linear Interaction Energy (LIE) method was used to estimate the free-energy of ATP binding to wild-type and mutant Kir6.2 channels. Comparisons of the theoretical binding free energies for ATP with those determined from mutational experiments enabled the identification of the most probable conformation of ATP bound to the Kir6.2 channel. A set of LIE parameters was defined that may enable prediction of the effects of additional Kir6.2 mutations within the ATP binding site on the affinity for ATP.